Validity and calibration of the FFQ used in the Melbourne Collaborative Cohort Study. Issue 13 (14th April 2016) - Bassett, Julie K; English, Dallas R; Fahey, Michael T; Forbes, Andrew B; Gurrin, Lyle C; Simpson, Julie A; Brinkman, Maree T; Giles, Graham G; Hodge, Allison M
Abstract: Objective: To evaluate the reliability and validity of the FFQ administered to participants in the follow-up of the Melbourne Collaborative Cohort Study (MCCS), and to provide calibration coefficients. Design: A random sample stratified by country of birth, age, sex and BMI was selected from MCCS participants. Participants completed two FFQ and three 24 h recalls over 1 year. Reliability was evaluated by intraclass correlation coefficients (ICC). Validity coefficients (VC) were estimated from structural equation models and calibration coefficients obtained from regression calibration models. Setting: Adults born in Australia, Greece or Italy. Subjects: Nine hundred and sixty-five participants consented to the study; of these, 459 participants were included in the reliability analyses and 615 in the validity and calibration analyses. Results: The FFQ showed good repeatability for twenty-three nutrients with ICC ranging from 0·66 to 0·80 for absolute nutrient intakes for Australian-born and from 0·51 to 0·74 for Greek/Italian-born. For Australian-born, VC ranged from 0·46 (monounsaturated fat) to 0·83 (Ca) for nutrient densities, comparing well with other studies. For Greek/Italian-born, VC were between 0·21 (Na) and 0·64 (riboflavin). Calibration coefficients for nutrient densities ranged from 0·39 (retinol) to 0·74 (Mg) for Australian-born and from 0·18 (Zn) to 0·54 (riboflavin) for Greek/Italian-born. Conclusions: The FFQ used in the MCCS follow-up study is suitable for estimating energy-adjusted nutrients for Australian-born participants. However, its performance for estimating intakes is poorer for southern European migrants and alternative dietary assessment methods ought to be considered if dietary data are to be measured in similar demographic groups.